Temperature measurements with two different IR sensors in a continuous-flow microwave heated system - Rydfjord, Jonas; Svensson, Fredrik; Fagrell, Magnus; Sävmarker, Jonas; Thulin, Måns; Larhed, Mats (Beilstein Journal of Organic Chemistry, 2013)
In a continuous-flow system equipped with a nonresonant microwave applicator we have investigated how to best assess the actual temperature of microwave heated organic solvents with different characteristics. This is non-trivial as the electromagnetic field will influence most traditional methods of temperature measurement. Thus, we used a microwave transparent fiber optic probe, capable of measuring the temperature inside the reactor, and investigated two different IR sensors as non-contact alternatives to the internal probe. IR sensor 1 measures the temperature on the outside of the reactor whilst IR sensor 2 is designed to measure the temperature of the fluid through the borosilicate glass that constitutes the reactor wall. We have also, in addition to the characterization of the before mentioned IR sensors, developed statistical models to correlate the IR sensor reading to a correct value of the inner temperature (as determined by the internal fiber optic probe), thereby providing a non-contact, indirect, temperature assessment of the heated solvent. The accuracy achieved with these models lie well within the range desired for most synthetic chemistry applications.
Keywords: continuous-flow; flow chemistry; heating; microwave; organic synthesis; temperature

(untitled) - Kappe, C. O.; Pieber, B.; Dallinger, D. (Angew. Chem., Int. Ed., 2013)

(untitled) - Dudley, G. B.; Stiegman, A. E.; Rosana, M. R. (Angew. Chem., Int. Ed., 2013)

(untitled) - Kappe, C. O. (Angew. Chem., Int. Ed., 2013)

(untitled) - Caddick, S.; Fitzmaurice, R. (Tetrahedron, 2009)

Microwaves in Organic and Medicinal Chemistry - Kappe, C. O.; Stadler, A.; Dallinger, D. (Wiley-VCH Verlag GmbH & Co. KGaA, 2012)

(untitled) - Gising, J.; Odell, L. R.; Larhed, M. (Org. Biomol. Chem., 2012)

(untitled) - Stone-Elander, S. A.; Elander, N.; Thorell, J.-O.; Solås, G.; Svennebrink, J. (J. Labelled Compd. Radiopharm., 1994)

(untitled) - Strauss, C. R.; Trainor, R. W. (Aust. J. Chem., 1995)

(untitled) - Schanche, J.-S. (Mol. Diversity, 2003)

Microwaves in Organic and Medicinal Chemistry - Kappe, C. O.; Stadler, A.; Dallinger, D. (Equipment Review, 2012)

(untitled) - Gedye, R. N.; Smith, F. E.; Westaway, K. C. (Can. J. Chem., 1988)

(untitled) - Mingos, D. M. P.; Baghurst, D. R. (Chem. Soc. Rev., 1991)

(untitled) - Gabriel, C.; Gabriel, S.; Grant, E. H.; Halstead, B. S. J.; Mingos, D. M. P. (Chem. Soc. Rev., 1998)

(untitled) - Langa, F.; de la Cruz, P.; de la Hoz, A.; Díaz-Ortiz, A.; Díez-Barra, E. (Contemp. Org. Synth., 1997)

Chemistry Under Extreme and Non-Classical Conditions - Mingos, D. M. P.; Whittaker, A. G. (Microwave Dielectric Heating Effects in Chemical Synthesis, 1997)

(untitled) - Kappe, C. O. (Chem. Soc. Rev., 2013)

(untitled) - Öhrngren, P.; Fardost, A.; Russo, F.; Schanche, J.-S.; Fagrell, M.; Larhed, M. (Org. Process Res. Dev., 2012)

(untitled) - Fardost, A.; Russo, F.; Larhed, M. (Chim. Oggi, 2012)

OptrisGmbH optris® CSmicro 3M

OptrisGmbH Basic Principles of Non-Contact Temperature Measurement

(untitled) - Kappe, C. O. (Angew. Chem., Int. Ed., 2004)

(untitled) - Bremberg, U.; Lutsenko, S.; Kaiser, N.-F.; Larhed, M.; Hallberg, A.; Moberg, C. (Synthesis, 2000)

(untitled) - Nilsson, P.; Gold, H.; Larhed, M.; Hallberg, A. (Synthesis, 2002)